Acute surgical abdomen due to duodenal perforation in an elderly COVID-19 patient - Džemail Detanac; Enes Zogić; Džemil Bihorac; Dženana Detanac; Lejla Ćeranić; Mehmed Mujdragić; Kemal Alihodžić; Irfan Ćorović (Биомедицинска истраживања, 2021)
Introduction: Since the announcement of the SARS-CoV-2 pandemic, the health system has been facing great challenges. Due to several uncertainties and concerns, surgeons face a huge challenge in solving urgent surgical conditions in order to save a life. Case report. We present a patient with a coronavirus (COVID-19) infection and acute abdomen who was in poor general condition at the time of surgery, septic, all as a result of duodenal ulcer perforation. She did not have a positive RT-PCR at the time of surgery, but the lung CT scan showed highly indicative signs of COVID-19 infection. She had a positive nasopharyngeal swab RT-PCR test for the SARS-CoV-2 virus on the first postoperative day. Conclusion: All suspected COVID-19 patients during surgery should be treated as positive for SARS-CoV-2 virus with the use of all staff protection measures.
Keywords: COVID-19; acute abdomen; RT-PCR; CT